2018
DOI: 10.2460/ajvr.79.5.532
|View full text |Cite
|
Sign up to set email alerts
|

Thromboelastographic evaluation of dogs bitten by rattlesnakes native to southern California

Abstract: OBJECTIVE To validate that dogs become hypocoagulable following rattlesnake envenomation and to determine whether thromboelastographic abnormalities are correlated with envenomation severity for dogs bitten by rattlesnakes native to southern California. ANIMALS 14 dogs with observed or suspected rattlesnake envenomation (envenomated dogs) and 10 healthy control dogs. PROCEDURES For each dog, a citrate-anticoagulated blood sample underwent kaolin-activated thromboelastography. For each envenomated dog, a snakeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(33 citation statements)
references
References 21 publications
1
32
0
Order By: Relevance
“…This phenomenon is termed venom-induced consumptive coagulopathy (VICC) because of its shared similarity with disseminated intravascular coagulopathy (DIC); however, it does not trigger severe organ damage or systemic thrombosis, which is common in DIC [13]. Animals with VICC usually exhibit pathological abnormalities, such as prolonged prothrombin time (PT), activated partial thromboplastin time (aPTT), low fibrinogen and antithrombin concentrations, elevated D-dimer levels, and thrombocytopenia [14][15][16][17]. However, laboratory results of classical coagulation tests (CCTs) are frequently normal in the initial stages and gradually become abnormal within a few hours to days [14,18,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon is termed venom-induced consumptive coagulopathy (VICC) because of its shared similarity with disseminated intravascular coagulopathy (DIC); however, it does not trigger severe organ damage or systemic thrombosis, which is common in DIC [13]. Animals with VICC usually exhibit pathological abnormalities, such as prolonged prothrombin time (PT), activated partial thromboplastin time (aPTT), low fibrinogen and antithrombin concentrations, elevated D-dimer levels, and thrombocytopenia [14][15][16][17]. However, laboratory results of classical coagulation tests (CCTs) are frequently normal in the initial stages and gradually become abnormal within a few hours to days [14,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Its usefulness ranges from transfusion in trauma patients to monitoring hemostasis during liver transplantation and cardiac surgeries [21,22]. In veterinary medicine, researchers have reported on the use of TEG during the diagnosis and treatment of VICC along with CCTs [14][15][16][17]. However, they have not compared the efficacy of TEG with that of CCTs.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] More specific conditions relevant to that presented herein include TEG evaluation of hemostatic function in dogs with DIC, the use of TEG to assess hemostatic changes in dogs naturally envenomed by the African puffadder (Bitis arietans) and snouted cobra (Naja annulifera), and TEG evaluation of dogs bitten by rattlesnakes native to southern California. [14][15][16] The use of TEG in cases of boomslang envenomation in people has been reported; however, to the authors' knowledge, no such reports exist in the veterinary literature. (or sometimes referred to as stage IV of DIC).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, TEG has grown in popularity and has subsequently been demonstrated to be a useful tool in both the diagnosis and management of various hemostatic abnormalities in dogs, correlating with clinical signs of bleeding 11–13 . More specific conditions relevant to that presented herein include TEG evaluation of hemostatic function in dogs with DIC, the use of TEG to assess hemostatic changes in dogs naturally envenomed by the African puffadder ( Bitis arietans ) and snouted cobra ( Naja annulifera ), and TEG evaluation of dogs bitten by rattlesnakes native to southern California 14–16 …”
Section: Discussionmentioning
confidence: 99%
“…Thromboelastographic evaluation of dogs bitten by rattlesnakes revealed that most envenomated animals had a clot strength below the 25th percentile (compared to control dogs), suggestive of a hypocoagulable state. 11 Rattlesnake venom is also reported to damage the endothelium and basement membrane of blood vessels and results in localized rhabdomyolysis. The gross and histologic findings in our warty pig cases are consistent with those described for rattlesnake envenomation in other species.…”
mentioning
confidence: 99%